Pomiędzy Sherlockiem Holmesem a Eberhardem Mockiem: Hotel „Wielkie Prusy” Bohdana Kołomijczuka - Zywert, Aleksandra (Studia Ukrainica Posnaniensia, 2022)
The subject of the analysis in this paper is the novel by Bohdan Kolomiichuk entitled The Great Prussia Hotel. From the genre point of view, the piece fits seamlessly into the so-called retro detective story with elements of the noir novel. The author’s variant of the retro detective story is clearly inspired by the classics of the genre, such as Artur Conan Doyle or Agata Christie (also contemporary ones, already containing further original modifications, such as Marek Krajewski or Konrad Lewandowski). This translates, for example, into the construction of the main character. Thus, a hybrid character is created, which appears to be a conglomerate of the features of Sherlock Holmes and Eberhard Mock. One should also pay attention to the construction of the novel space. Mapping activates various cultural and historical codes, it is not only an element accompanying the development of the plot but an expression of counter-hegemonic practice - the opposition to superficial top-down unification, anonymization and denationalization. Kolomiichuk’s novel can therefore be considered a borderland work in some places due to its multi-address character and a certain historical verve. In this context, at times drifting somewhat towards postmodernism, the Hotel smoothly fits into the trend of opening up popular literature to hybridity, borderline and multi-genre, visible since the turn of the 20th and 21st century, while taking into account national archetypes, images and motifs, and correlating them with the global (also contemporary) classics of the genre.